El Excentrico, 1956-10-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
October 5, 1956 [5 de octubre de 1956]. Ano 7, No. 3. Cover contains a photo of Norma Minjarez, a reporter who was new to El Excentrico's staff at the time of this issue's release. The headline reads, "Reporter Norma Minjarez joins EXCENTRICO'S Staff."